A experiência prévia de monitores do projeto de extensão Atividades Ginásticas: facilidades e dificuldades - Andreolli, Marcelle [UNESP]; Vargas, Cinthia Reis [UNESP]; Lima, Letícia Bartholomeu de Queiroz [UNESP]; Murbach, Marina Aggio [UNESP]; Deutsch, Silvia [UNESP]; Schiavon, Laurita Marconi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The current research aims to analyze aspects related to difficulties and facilities of the monitors of the extension project “Atividades Ginásticas” related to planning and teaching, based on their prior experiences with gymnastics, from experience reports. The reports were performed by two monitors of the extension project, one with prior experience with gymnastics and another without any prior experience in this area. It was observed that prior experience with gymnastics or lack of it wasn’t an obstacle to performance as monitor in the gymnastics’ extension project and that prior experience as a gymnast appears as facilitator in teaching elements related to gymnastics’ technical aspects. However, others prior experiences, not directly related to the gymnastics, also showed to be important, with different contributions to the project. Is known the limitation of the reduced number of research participants, although it is a research exercise as a pilot study for future expansion.

A presente pesquisa tem como objetivo analisar aspectos relacionados às dificuldades e facilidades dos monitores do projeto de extensão “Atividades Ginásticas” referentes ao planejamento e a docência nas aulas, baseados em suas experiências prévias com a Ginástica, a partir de relatos de experiência. Os relatos foram realizados por duas bolsistas do referido projeto de extensão, sendo uma com experiência prévia com modalidades gímnicas e outra sem qualquer experiência prévia nesta área. Observou-se que a experiência prévia com a Ginástica ou a falta dela não mostrou-se como um empecilho para a atuação como monitor no projeto de extensão em Ginástica e, que a experiência prévia como ginasta aparece como facilitadora no ensino de elementos relacionados a aspectos técnicos da Ginástica. Porém, outras experiências prévias, não relacionadas diretamente com a Ginástica, também mostraram-se importantes, com contribuições distintas para o projeto. Sabe-se da limitação do número pequeno de sujeitos da pesquisa, mas trata-se de um exercício de investigação como piloto para posterior ampliação.
Keywords: Extension courses; Gymnastics; Prior experiences; Cursos de extensão; Ginástica; Experiências prévias